Murder in purple and gold - Davis, Lindsey (Davis, Lindsey. Flavia Albia mystery, 2026)
When Flavia Albia stumbles upon the murdered corpse of a young man near Rome's famous Circus Maximus, she is about to embark on one of her most dangerous and complicated cases. Rome and the Romans are obsessed with chariot racing. Lepo was the rising star of the Purples, a new team created by the psychotic Emperor Domitian with big money backing. Suspicion immediately falls on Lepo's greatest rival, Agathon, a young man emerging from a rival team, the Golds. Convinced of his guilt, a lynch mob is hunting him. The Golds faction hire Flavia to clear their man's name. He appears to have an alibi for the night of the murder but, as Flavia soon finds out, nothing is as it seems in the dangerous and glamorous world of the charioteers in which fortunes can be won or lost in seconds and violent death in the arena is always just one race away.